Local political climate and spill-over effects on refugee and migrant health: a conceptual framework and call to advance the evidence - Bozorgmehr, Kayvan; Kühne, Simon; Biddle, Louise (BMJ global health, 2023)
The health of refugees and migrants is determined by a wide range of factors. Among these, the local political climate in the postmigration phase is an important determinant which operates at interpersonal and institutional levels. We present a conceptual framework to advance theory, measurement and empirical evidence related to the small-area factors which shape and determine the local political climate, as these may translate into variations in health outcomes among refugees, migrants and other marginalised population groups. Using the example of Germany, we present evidence of small-area variation in factors defining political climates, and present and discuss potential pathways from local political climates to health outcomes. We show that anti-immigrant and antirefugee violence is a Europe-wide phenomenon and elaborate how resilience of individuals, communities, and the health system may function as moderator of the effects of the local political climate on health outcomes. Building on a pragmatic review of international evidence on spill-over effects identified in other racialised groups, we present a conceptual framework which incorporates direct effects as well as ‘spill-over’ effects on mental health with the aim to spark further academic discussion and guide empirical analysis on the topic. After presenting and discussing methodological challenges, we call for collective efforts to build coalitions between social sciences, conflict and violence studies, political science, data science, social psychologists and epidemiology to advance theory, measurement, and analysis of health effects of local political climates.
Gesehen am 25.07.2023